Envisioning native forest conservation policy: an integrated assessment using discrete multicriteria decision analysis and a participatory approach - Tello, Diego Sebastián; De Prada, Jorge Dante; Cristeche, Estela Raquel (2019)
The objetive is to design an devaluate exante alternatives for native forest conservation policies in the Caldén Biogeographic Corridor (CBC) area, in the Province of Córdoba, Argentina combining Cost Benefit Analysis (CBA) and Multicriteria Decision Analysis (MCDA).